Host–Guest Thin Films by Confining Ultrafine Pt/C QDs into Metal‐Organic Frameworks for Highly Efficient Hydrogen Evolution. Issue 45 (20th October 2020) - Xiao, Yi‐Hong; Tian, Wenming; Jin, Shengye; Gu, Zhi‐Gang; Zhang, Jian
Abstract: Combining the features of host templates and guest species is an efficient strategy to optimize the photo/electrocatalytic performance. Herein, novel host–guest thin‐film electrocatalysts are designed and developed with Pt doped carbon (Pt/C) confined into porphyrin‐based metal‐organic frameworks (MOFs). Porous MOF PCN‐222 and PCN‐221 thin films are used as the host templates and fabricated using vapor‐assisted deposition method, and then the guest Pt/C quantum dots are encapsulated into the MOFs by loading the glucose mixed H2 PtCl6 and heating at 200 °C. Thanks to the confinement effect of MOF pores, the homogenous and ultrafine Pt/C nanowires (Pt/CNWs) and nanodots (Pt/CNDs) are confined in nanochannels of PCN‐222 and nanocages of PCN‐221 (Pt/CNW@PCN‐222 and Pt/CND@PCN‐221), respectively. The electrocatalytic study shows that the host–guest thin films have highly‐efficient electrocatalytic hydrogen evolution performance under light irradiation. Furthermore, the time‐resolved photoluminescent results reveal that Pt/CNW@PCN‐222 has a faster charge transfer (441 ps) from PCN‐222 to Pt/CNWs comparing to that (557 ps) of Pt/CND@PCN‐221, indicating the guests with different shapes play an important role in the electrocatalytic performance. This work serves to present both the outstanding level of control in the precise synthesis and high potential for nanocomposite thin films in photo‐electrocatalytic application. Abstract : Novel host–guest thin‐film electrocatalysts by confining ultrafine Pt doped carbon nanowires and carbon nanodots in porphyrin‐based metal‐organic frameworks with nanochannels and nanocages are developed, respectively. The experimental results show that the unique host–guest thin films have highly‐efficient electrocatalytic hydrogen evolution performance under light irradiation and the guests with different shapes play an important role in the electrocatalysis.